Monocyte-T-cell interactions in pokeweed mitogen-activated cultures. - Pryjma, J (1990)
Monocyte-T-cell interactions were studied in pokeweed mitogen (PWM)-activated cell cultures. We addressed the question of monocyte changes in PWM-stimulated cultures of T cells and monocytes and found, by flow cytometric analysis, that PWM activation led to a loss of cells with monocyte or macrophage phenotype (CD14, HLA-DR, HLA-DQ) within 48 hr of culture in the presence of T cells (CD4+ T cells), but not in cultures of pure monocytes. Chemiluminescence measurements revealed that phagocytic stimulation of monocytic superoxide release was impaired in PWM-stimulated cultures of monocytes plus T cells, but not in PWM-stimulated cultures of pure monocytes. Furthermore, PWM induced the secretion of interferon-gamma (IFN-gamma) in primary cultures of T cells supplemented with 20% of monocytes, whereas in subsequent secondary cultures of these cells PWM induced IFN-gamma only when monocytes were added. We conclude from these flow cytometric and functional analyses that monocytes are efficiently eliminated from PWM-activated T-cell/monocyte cultures by CD4+ T lymphocytes.